Locus of Control and Self-Concept as Determinants of Internet AddictionamongPublic University Undergraduates in Oyo State (Educational Psychology Journal, 2023)
The study investigated locus of control and self-concept as determinants of internet addiction among public university undergraduates in Oyo State. Four hundred University Undergraduates were selected through stratified random sampling techniques which were used in sampling participants from two selected public universities in Oyo state. To achieve the objectives, the respondents were measured with relevant adopted standardized scales such as Self-Concept Scale, Locus of Control Scale and Internet Addiction Scale. Four research hypotheses were tested in the study through Pearson Product Moment Correlation and Multiple Regression analysis. Results showed that there was a significant relationship between locus of control and internet addiction (r=0.12; p<0.05), there was a significant relationship between self-concept and internet addiction (r=0.66; p<0.05), there is a joint effect between locus of control, self-concept and internet addiction (F 2,397=148.020; p<0.05) while locus of control do not statistically predict internet addiction (t=0.618, p>0.05) and self-concept statistically predict internet addiction (t=16.942; p<0.05). The study recommends among others that school counsellors and policy makers should organize seminars, workshop and conferences to sensitize the studentsof the need to have realistic and objective self-assessment and self-concept.